Sensitivity Training: An Established Management Development Tool? - Kearney, William J.; Martin, Desmond D. (Academy of Management Journal, 1974)
The article looks at a questionnaire of personnel directors regarding state of sensitivity training as utilized within large scale business firms. Techniques used to improve organizational effectiv...